Religious Processions: Urban Politics and Poetics - Kong, Lily (Institutional Knowledge at Singapore Management University, 2005)
In this paper, I will explore the ways in which processions, by their very visibility, foreground the relationships between the secular and the sacred, while contributing to a construction of identity and community, and simultaneously surfacing fractures therein. Using the example of multireligious yet secular Singapore, I will examine (a) the state's management of religious processions, including the regulation of time and space for such events, as well as regulations over noise production; (b) the tactics of adaptation, negotiation and resistance that participants engage in at an everyday level in response to the state's ideologies, policies, laws and strategies; (c) the participants' experience of these processions in terms of the sense of communitas that Turner describes but which Eade and Sallnow dispute, through emphasis on faultlines within "community", based on age, class and nationality; (d) the investment of sacred meanings in these processions by participants and the nature of their "sacred experience"; and (e) the manner in which such activities, associated state actions and participants' responses evoke reactions from non-participants within and beyond the specific religious group, exploring variations, from obvious fractures between groups to curiosity to enthusiastic support. My specific case focuses on Thaipusam processions in Singapore as one of the most colourful, organized and long-lasting religious processions.